Teacher Satisfaction in High Poverty Schools: Searching for Policy Relevant Interventions in Estonia, Georgia, and Latvia - William Smith; Anna Persson (Voprosy obrazovaniya / Educational Studies Moscow, 2016)
Provided the shared post-soviet context and the rapidly declining school age population, this comparative study of teachers in Estonia, Georgia, and Latvia can shed light on alternative approaches to increased teacher satisfaction for countries in similar contexts that are unable to make across the board increases in teacher salary. The focus on high poverty schools is essential in these countries as the changing demographics and present school funding mechanisms disproportionately affect rural schools which are often high poverty. This study addresses two pressing research questions, exploring each independently for Estonia, Georgia, and Latvia: 1) How does teacher satisfaction and other teacher characteristics differ by school poverty level? 2) What policy relevant factors are related to increased satisfaction for teachers in high poverty schools? Data from the 2013 Teaching and Learning International Survey (TALIS) were used in this study. Given the dichotomous measures of the outcome variable (teacher satisfaction), hierarchical generalized linear modeling (HGLM) was the primary method of analysis. Although the policy  implementation and internalization process is challenging, this study indicates that simplistic, externally driven policy solutions, such as introducing induction programs or changing the contract status of teachers, are not as effective in increasing teacher satisfaction as investments that contribute to a positive school climate where teachers feel valued and included as professionals.